A randomized control trial investigating the effects of a play-informed care-giver implemented home-based intervention on playfulness for HIV positive children aged 10 months to 8 years on HAART from a low socio-economic status - Uys, Anandé (Division of Occupational Therapy, 2016)
Introduction: Play is foundational to learning and well-being, and prepares children for functional participation later in life. Playfulness forms a critical aspect to play, and describes a general disposition to play. There is currently no reported research study on playfulness levels for children with HIV/AIDS. The play needs of this population are therefore not adequately understood. The play-informed caregiver implemented home-based intervention (PICIHBI) was developed by pediatric occupational therapists as part of occupation-centred occupational therapy practice. PICIHBI appears to have potential for promoting play and development in children with HIV/AIDS who have been on Highly Active Anti-Retroviral Treatment (HAART) since early childhood. The current study forms part of a larger project investigating the effects of a play-informed caregiver implemented home-based intervention on participation outcomes for HIV positive children on HAART and living in families with low socio-economic status (SES). Objectives: This study aimed to establish a playfulness profile for HIV positive children on HAART as well as compare differences in playfulness between children with HIV on HAART since early childhood attending traditional one-on-one occupational therapy, and those attending PICIHBI.